Cytocompatibility and cellular interactions of chondroitin sulfate microparticles designed for inhaled tuberculosis treatment - Rodrigues, Susana (2021)
Tuberculosis remains a leading cause of death, therapeutic failure being mainly due to non-compliance with prolonged treatments, often associated with severe side-effects. New therapeutic strategies are demanded and, considering that the lung is the primary site of infection, direct lung delivery of antibiotics is possibly an effective approach. Therapeutic success in this context depends on suitable carriers that reach the alveoli where Mycobacterium hosts (macrophages) reside, as well as on their ability to promote macrophage capture and intracellular accumulation of drugs. In this work, we propose inhalable polymeric microparticles produced from chondroitin sulfate, a polymer composed by moieties recognized by macrophage receptors. Spray-drying of chondroitin sulfate in combination with two first-line antitubercular drugs (isoniazid and rifabutin) yielded respirable microparticles that evidenced no cytotoxic effects on lung epithelial cells (A549) and macrophages (dTHP1 and J744A.1). The microparticles exhibited tendency for macrophage capture in a dose-dependent manner, which was validated through imaging. High content image analysis revealed that rifabutin induced a dose-dependent increase in phospholipid content of macrophages, which could be prevented by formulation in chondroitin sulfate microparticles. This work provides indications on the potential of chondroitin sulfate carriers to interact with macrophages, thus providing a platform for drug delivery in the context of macrophage intracellular diseases, namely tuberculosis.